How could science-interfaces boost food system transformation? - Hainzelin, Etienne; Caron, Patrick; Place, Frank; Alpha, Arlène; Dury, Sandrine; Echeverria, Ruben G.; Harding, Amanda (United Nations Food Systems Summit, 2021)
The world’s food systems must be transformed to make healthier diets more accessible for all, while increasing the sustainability and resilience of these systems, as clearly called for in the 2030 Agenda for Sustainable Development. Scientists and policymakers are among the complex set of actors necessary for this transformation. Working together, they could become a real powerhouse for food system transformation. This brief reviews the importance of the interfaces between science and and how these interfaces can become more active and effective. It is based on the synthesis and recommendations of the high-level event Bonding Science and to Accelerate Food Systems Transformation, held on February 4, 2021, to contribute to the upcoming United Nations Food Systems Summit (UNFSS) that made a strong call to action to both the science and communities.